Two deletions overlapping a distant FOXF1 enhancer unravel the role of lncRNA LINC01081 in etiology of alveolar capillary dysplasia with misalignment of pulmonary veins. Issue 8 (19th May 2014) - Szafranski, Przemyslaw; Dharmadhikari, Avinash V.; Wambach, Jennifer A.; Towe, Chris T.; White, Frances V.; Grady, R. Mark; Eghtesady, Pirooz; Cole, F. Sessions; Deutsch, Gail; Sen, Partha; Stankiewicz, Paweł
<x xml:space="preserve">Abstract</x> Position effects due to disruption of distant cis‐regulatory regions have been reported for over 40 human gene loci; however, the underlying mechanisms of long‐range gene regulation remain largely unknown. We report on two patients with alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) caused by overlapping genomic deletions that included a distant FOXF1 transcriptional enhancer mapping 0.3 Mb upstream to FOXF1 on 16q24.1. In one patient with atypical late‐onset ACDMPV, a ∼1.5 Mb deletion removed the proximal 43% of this enhancer, leaving the lung‐specific long non‐coding RNA (lncRNA) gene LINC01081 intact. In the second patient with severe neonatal‐onset ACDMPV, an overlapping ∼194 kb deletion disrupted LINC01081. Both deletions arose de novo on maternal copy of the chromosome 16, supporting the notion that FOXF1 is paternally imprinted in the human lungs. RNAi‐mediated knock‐down of LINC01081 in normal fetal lung fibroblasts showed that this lncRNA positively regulates FOXF1 transcript level, further indicating that decrease in LINC01081 expression can contribute to development of ACDMPV. © 2014 Wiley Periodicals, Inc.